2018
DOI: 10.9734/ijpss/2018/44508
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Diversity and Vegetation-Soil Correlations in Wadi Qusai, Jazan, Saudi Arabia

Abstract: Aims: To study Floristic diversity, life-form, chorology, edaphic factors affecting the species distribution of Wadi Qusai. Study Design: Several field trips were carried out to the study area -sites soil analysis. Place and Duration of Study: Wadi Qusai -Jazan -Saudi Arabia. Methodology: Floristic composition, vegetation diversity, life form, chorology, soil analysis and cover estimation by TWINSPAN, DCA and CCA. Results: A total of 103 species belonging to 77 genera and 33 families were recorded from 20 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
3
1
Order By: Relevance
“…Chorological analysis of the 341 species surveyed in the study area revealed that the biregional elements of the Saharo-Arabian/Sudano-Zambezian chorotype (35.48%) are the most dominant chorotypes, forming the major constituent (about two-thirds of the recorded plants) of the floristic structure in Jabal Fayfa. Similar results were obtained in different studies of the flora of Saudi Arabia [21,26,29,31,62,74,75]. However, the dominance of the biregional Saharo-Arabian/Sudano-Zambezian chorotype (35.48%) over the pluri-and monoregional chorotypes (19.94% and 12.32%, respectively) disagrees with the findings of [76].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Chorological analysis of the 341 species surveyed in the study area revealed that the biregional elements of the Saharo-Arabian/Sudano-Zambezian chorotype (35.48%) are the most dominant chorotypes, forming the major constituent (about two-thirds of the recorded plants) of the floristic structure in Jabal Fayfa. Similar results were obtained in different studies of the flora of Saudi Arabia [21,26,29,31,62,74,75]. However, the dominance of the biregional Saharo-Arabian/Sudano-Zambezian chorotype (35.48%) over the pluri-and monoregional chorotypes (19.94% and 12.32%, respectively) disagrees with the findings of [76].…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, a floristic analysis of vascular plant species from the study area includes 341 species belonging to 240 genera and 70 families (Appendix A). Compared to the floristic composition of different hotspot regions in Jizan of Saudi Arabia, species numbers recorded in this study were very high [26,[29][30][31]34,54]. However, the number of species recorded in this study (341 taxa) is within the range of the flora recorded previously by [35].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Progressive land degradation and continuous biodiversity loss define huge challenges for healthy ecosystem functioning in many countries all over the world [1]. Climate change, drought periods, frequent extreme events, the overexploitation of natural resources, and inappropriate management measures have induced short-and long-term adverse impacts on different environmental components, namely soil fertility and plant diversity [2][3][4][5]. These impacts have commonly been observed and they have induced irreversible effects inhibiting the rehabilitation of the degraded resources and the restoration of pristine conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies of land degradation assessment in the Tunisian rangelands have used (1) localized field measurements with restraint application and a limited analysis of ecosystem dynamics or (2) remote sensing data as a non-destructive solution for these limits. In the context of these shortcomings, this study aims to evaluate the wind erosion impact control measures on the degraded ecosystems of the study area (SE Tunisia) via an integrated approach that combines field measurements and remote sensing data over an extended period (2020-2023).…”
Section: Introductionmentioning
confidence: 99%